Regional financial characteristics and public transparency towards frequency of fraud in the local government - Yeni Priatnasari; Djoko Suhardjanto (Universitas Hayam Wuruk Perbanas, 2020)
It has been noted that Corruption in Indonesia today has become a crucial problem that cannot be underestimated. Some news about the occurrence of corruption in the local government is quite concerned. This study aims to look at the influence of both financial characteristics and regional public transparency towards fraud frequency in local governments at the provincial level. This research was carried out by quantitative descriptive method by looking at local government financial report data and reports from ACCH (Anti Corruption Clearing House). This study used secondary data, namely in the form of Indonesia Provincial Government’s financial statements and the results of the ACCH report in 2017. The results of this study are expected to provide advice and input in regional financial governance in all the province to be able to reduce frequency fraud in local governments